Hydrodynamics in Evaporate-Bearing Fine-Grained Successions Investigated through an Interdisciplinary Approach: A Test Study in Southern Italy—Hydrogeological Behaviour of Heterogeneous Low-Permeability Media. (8th May 2018) - Petrella, E.; Bucci, A.; Ogata, K.; Zanini, A.; Naclerio, G.; Chelli, A.; Francese, R.; Boschetti, T.; Pittalis, D.; Celico, F.
Abstract : Messinian evaporates are widely distributed in the Mediterranean Sea as outcropping sediments in small marginal basins and in marine cores. Progressive filling of subbasins led to the formation of complex aquifer systems in different regions where hypersaline and fresh water coexist and interact in different manner. It also generates a significant diversification of groundwater hydrochemical signature and different microbial communities. In the case study, the hydrogeology and hydrochemistry of the whole system are influenced by good hydraulic connection between the shallower pyroclastic horizon and the underlying evaporate-bearing fine-grained Messinian succession. This is demonstrated by the merge of hydrogeological, chemical, isotopic, and microbiological data. No mixing with deep ascending waters has been observed. As shown by geophysical, hydraulic, and microbiological investigations, the hydraulic heterogeneity of the Messinian bedrock, mainly due to karstified evaporitic interstrata/lenses, causes the hydraulic head to significantly vary with depth. Somewhere, the head increases with the depth's increase and artesian flow conditions are locally observed. Moreover, the metagenomic investigations demonstrated the existence of a poor hydraulic connection within the evaporate-bearing fine-grained succession at metric and decametric scales, therefore leading to a patchwork of geochemical (and microbiological) subenvironments.